Description of breastfeeding on hyperbilirubinemia infants with light therapy in the perinatology room of Muhammadiyah Hospital Taman Puring - Mustikawati, Mustikawati; Hikma, Wd Erty; Fiandy, Rani Pratiwi; Fitriani, Vany (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Hyperbilirubinemia is a condition where excessive bilirubin builds up in the blood, causing yellowing of the skin, sclera, and nails. Hyperbilirubinemia is a common finding in newborns and will start appearing clinically in newborns when blood bilirubin levels are 5 – 7 mg/dl. hyperbilirubinemia can be caused by several factors, including gestational age, birth weight, blood type, breast milk intake, prematurity, and congenital diseases or disorders.  Objectives: to describe how breastfeeding could help reduce bilirubin levels in infants with hyperbilirubinemia receiving light therapy in the Perinatology Room at Muhammadiyah Hospital Taman Puring. Methods: the research used a qualitative descriptive approach, collecting data through interviews, observations, and documentation. The inclusion criteria in this research are: hyperbilirubinemia infants with phototherapy, exclusive breastfeeding, no comorbidities and parents willing to have their infants become case study subjects. The study involved three infants aged 3-7 days with hyperbilirubinemia who were given breastfeeding and light therapy. Results: showed that infants who underwent light therapy for 24 to 48 hours, combined with breastfeeding tailored to their fluid needs based on body weight (169 ml/day for a 2700-gram baby, 320 ml/day for a 3200-gram baby, and 465 ml/day for a 3150-gram baby), experienced a significant reduction in bilirubin levels. Conclusions: breastfeeding and light therapy resulted in a notable decrease in serum bilirubin levels in hyperbilirubinemia infants. The study recommended that nurses promote exclusive breastfeeding and ensure the breastfeeding process was effective and met the infants’ needs to help lower bilirubin levels.